Analisis Kinerja Instalasi Farmasi RSU Universitas Muhammadiyah Malang dengan Pendekatan Balanced Scorecard - Hidayati, Ika Ratna (Pharmaceutical Journal of Indonesia, 2022)
The Pharmacy Installation of the University of Muhammadiyah Malang Hospital has never conducted a performance measurement so it is not known how far the management has succeeded in achieving the organization's vision and goals. In addition, performance measurement is also needed to support the hospital accreditation process. This study was conducted to analyze the performance of the Pharmacy Installation of the University of Muhammadiyah Malang Hospital with a balanced scorecard approach from growth and learning perspective, internal business perspective and costumer perspective. This research was conducted in a non-experimental descriptive for growth and learning perspectives with research variables employee satisfaction, work spirit, and retention rate of IFRSU UMM employees. In the internal business perspective, the research was conducted observationally and analyzed descriptively with the research variables, dispensing time, level of drug availability, and drug information services. From the customer perspective was conducted in a non-experimental, quantitative analytical descriptive with research variables customer satisfaction and customer growth. The data was collected with retrospective and prospective methods. This research used both qualitative and quantitative data. Qualitative data was obtained by interview. Quantitative data was obtained by questionnaires and direct observation. The results of performance research on the growth and learning perspective of employee satisfaction indicators are satisfaction with a total value of 2,724, the indicator of work spirit is high with an average total score of 3.14 and the indicator of the retention rate of IFRSU UMM employees is at a normal value with an average turnover percentage of 7.88%. The results of the performance study on the internal business perspective showed that the dispensing time indicators for regular prescriptions is 22 minutes and 32 minutes for compound prescriptions. Percentage of drug availability is 100% and the results of the evaluation study of drug information services indicators have been implemented 100%, but there are information components that are not conveyed such as dosage, side effects, duration of use, and drug storage methods. The performance customer perspective of customer satisfaction indicators with the Servqual method obtained a negative gap value indicating customers are not satisfied. Analysis using the IPA method obtained the average percentage level of conformity showed was 93,00% where the results were in accordance with the Decree of the Minister of Health of the Republic of Indonesia Number 129 of 2008 concerning Hospital MSS. Analysis of customer growth indicators showed that the percentage results in 2019 were 101,39% and in 2020 it was 100,35%, exceeding the range of good criteria. It can be concluded the performance of the Pharmacy Installation of the University of Muhammadiyah Malang Hospital is quite good, but it is necessary to optimize and improvement.